Formulation design and in vitro evaluation of metformin hydrochloride transdermal film using hydrophilic polymer - Sinha, Neman; Gupta, Suchita; Choudhury, Ananta (Creative Pharma Assent, 2014)
The purpose of the experimental study was to design a sustained release film formulation of metformin hydrochloride. In this study a transdermal film has been prepared by incorporating hydrophilic polymers like HPMC and PVA in combination of different ratios. The prepared film were subjected for different evaluation parameters like swelling index study, surface pH, drug content analysis, thickness of film, folding endurance study, drug release study. Results of evaluation of all the film was found satisfactory. Again further study needs to be conducted to stabilize the formulations